Assessment of the dimensions and surface characteristics of orthodontic wires and bracket slots - Dolci,Gabriel Schmidt (2013)
OBJECTIVE: The purpose of this study was to evaluate the dimensions and surface characteristics of orthodontic wires and bracket slots of different commercial brands. METHODS: Thirty metallic brackets (0.022 x 0.028-in and 0.022 x 0.030-in) were divided in three groups: DYN/3M group = Dyna-Lock, 3M/Unitek (stainless steel, or SS); STD/MO group = Slim Morelli (SS); and Ni-Free/MO group = Slim Morelli (Ni-Free). The stainless steel wires (0.019 x 0.025in) were divided into two groups: MO group = Morelli; and 3M group = 3M/Unitek. The bracket and wire measurements were done by two methods: (a) Surface Electron Microscopy (SEM), and (b) Profile projection. The surface analysis was done qualitatively, based on SEM images and/or by a rugosimeter. The quantitative results were analyzed by ANOVA with Tukey's test (p < 0.05) and Student's t test. RESULTS: A significant difference in the dimensions of slots was observed, and the NiFree/MO group showed the greatest changes when compared to the other groups. The analysis of surface topography of the brackets indicated greater homogeneity of the metallic matrix for DYN/3M and STD/MO groups. As for the dimensions of the wires, groups showed statistically different mean heights. CONCLUSIONS: It was concluded that wires and brackets slots can present altered dimensions, which might directly and unintentionally affect the planned tooth movement.